Improvement on Direct Modulation Responses and Stability by Partially Corrugated Gratings Based DFB Lasers With Passive Feedback - Siti Sulikhah; San Liang Lee; Hen Wai Tsao (IEEE Photonics Journal)
DFB lasers with ultrashort cavities or integrated DFB lasers with passive waveguide reflectors are frequently proposed to realize directly modulated lasers (DMLs) for carrying ultrahigh data rate signals. The former suffers from poor heatsink and laser cleavage yield, while the single-mode stability of the latter scheme is seldom addressed. The mode selection and device performance of a DFB laser is well known to be very sensitive to the facet reflection and external optical feedback. The DFB lasers with partial corrugated gratings and passive feedback (PCG-PFL) are proposed here to overcome the challenging issues for the aforementioned two schemes. With PCG structure, the DFB lasers can maintain high single-mode yield (SMY) even with a high-reflection-coating on the rear facet and strong reflection from the integrated passive section. This provides the robustness in applying the integrated passive reflector to reshape the modulation response or to enhance the 3-dB bandwidth by using the photon-photon resonance (PPR) effect. By designing the PCG-PFL to have 150-μm long laser section, 50-μm long passive section, and 30% front-facet reflectivity, it can have about 86% of SMY, reduced resonant peak in the intensity modulation response, and reduced waveform overshoot and undershoot for transmitting 56-Gbaud/s PAM-4 signals. By using a longer passive reflector, enhanced bandwidth can be achieved by the PPR effect.